Social Anxiety in 15-19 Year Adolescents in Association with Their Subjective Evaluation of Mental and Physical Health - Ingrida Pilkionienė; Giedrė Širvinskienė; Nida Žemaitienė; Jolita Jonynienė (MDPI AG, 2021)
Background: Studies show that social anxiety in adolescence have negative impact on quality of life. The study evaluates social anxiety links with mental and physical health factors in adolescents aged 15-19 years. Methods: The research was performed in 2018 in secondary schools in Lithuania and included 1722 participants (46.1% males and 53.9% females). The social anxiety was assessed using Social Anxiety and Avoidance Scale for Adolescents. The main results were obtained using univariate and multivariate logistic regression analysis. Results: Total of 58.5% of adolescents were characterized by high social anxiety and 14.7% by high avoidance. Females more often were characterized by high anxiety compared to males. Multivariate logistic regression revealed that good mental health was a significant protective factor against high SA in adolescents. For females, high anxiety and avoidance were associated with living with both parents, for males, high anxiety was linked with mother's university education. Very common stomach and abdominal pain in females as well as severe and very common stomach or abdominal pain in males, increase the risk of major social anxiety. Conclusions: High social anxiety were more prevalent between females than males and was linked with various well-being and health aspects in adolescents.